1999
DOI: 10.1093/nar/27.16.3245
|View full text |Cite
|
Sign up to set email alerts
|

A chicken embryo protein related to the mammalian DEAD box protein p68 is tightly associated with the highly purified protein-RNA complex of 5-MeC-DNA glycosylase

Abstract: We have shown previously that DNA demethylation by chick embryo 5-methylcytosine (5-MeC)-DNA glycosylase needs both protein and RNA. Amino acid sequences of nine peptides derived from a highly purified 5-MeC-DNA glycosylase complex were identified by Nanoelectrospray ionisation mass spectrometry to be identical to the mammalian nuclear DEAD box protein p68 RNA helicase. Antibodies directed against human p68 helicase cross-reacted with the purified 5-MeC-DNA glycosylase complex and immunoprecipitated the glycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 46 publications
0
36
0
1
Order By: Relevance
“…The data suggest that p68 RNA helicase plays important roles in normal cell growth. Although, p68 RNA helicase was suspected of being involved in a number of biological processes in cells (8,12,17), the experimental evidence that links p68 RNA helicase to a specific cellular process is still 5 to 7). The extracts were pretreated with either RNase H and DNA oligonucleotide ␣U1 1-13 (lanes 3, 4, 6, and 7) or no RNase H treatment (lane 2 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest that p68 RNA helicase plays important roles in normal cell growth. Although, p68 RNA helicase was suspected of being involved in a number of biological processes in cells (8,12,17), the experimental evidence that links p68 RNA helicase to a specific cellular process is still 5 to 7). The extracts were pretreated with either RNase H and DNA oligonucleotide ␣U1 1-13 (lanes 3, 4, 6, and 7) or no RNase H treatment (lane 2 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…Both proteins may therefore participate in structural reorganization of ribonucleoprotein assemblies in vivo. In fact, p68 has been found in spliceosomes (15) and in a protein-RNA complex of 5-methylcytosine-DNA glycosylase (16). A recently reported (17) interaction with protein kinase A anchoring protein AKAP95 supports a role of p68 in hormonally responsive transcription complexes, and indeed, p68 and p72 act as transcriptional co-activators of estrogen receptor ␣ in cooperation with an RNA co-activator (18,19).…”
mentioning
confidence: 89%
“…Earlier work has shown that 5-methylcytosine was replaced by labeled cytosine during the demethylation reaction in erythroleukemia cells, indicating a replacement of the entire nucleotide or base alone (9). One potential mechanism to achieve this is through the action of 5-methylcytosine DNA glycosylase, which removes the methylcytosine from DNA leaving the deoxyribose intact (10). Local DNA repair then removes the abasic nucleotide and adds back an unmethylated cytosine nucleotide (11).…”
mentioning
confidence: 99%